The Economics of Retention: Exploring Shared Leadership in Emerging Markets - Dr. Zoya Wajid Satti; Dr. Nasir Munir; Hamiyat Yab; Muhammad Omair Khan; Jaweria Tariq (Indus Journal of Social Sciences, 2025)
Employee turnover poses a considerable burden for organisations, especially in the IT sector, where the fluidity of work intensifies the problem. This study examines the impact of shared leadership on turnover intentions, with job satisfaction and organisational commitment serving as mediators. Grounded in social network theory and social exchange theory, the study examines significant gaps by investigating the influence of shared leadership on promoting collaboration and commitment, hence decreasing turnover. The study utilises structural equation modelling to test its predictions based on data gathered from 354 employees in IT organisations in Pakistan. The findings indicate that shared leadership enhances organisational commitment, therefore decreasing turnover intention, however, the mediation effect of work satisfaction yields inconsistent outcomes. These insights highlight the capacity of shared leadership to improve staff retention, providing both theoretical improvements and practical solutions for enterprises in developing nations. This research endorses leadership methods that foster shared responsibility and sustainable organisational growth by harmonising with the United Nations Sustainable Development Goals.